2022
DOI: 10.1021/acsami.2c15514
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Paper Supercapacitors for Printed Wearable Electronics

Abstract: Printed paper-based electronics offers solutions to rising energy concerns by supplying flexible, environmentally friendly, low-cost infrastructure for portable and wearable electronics. Herein, we demonstrate a scalable spray-coating approach to fabricate tailored paper poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS)/cellulose nanofibril (CNF) electrodes for all-printed supercapacitors. Layer-by-layer spray deposition was used to achieve high-quality electrodes with optimized electrode th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Paper has unique advantages over other materials in terms of low cost, flexibility and self-driven fluid pumping, thus making it widely used in various fields of wearable devices and human health monitoring [ 88 , 89 , 90 , 91 , 92 ]. Paper-based microfluidics is a fast-growing field because the inherently porous structure of paper provides a separate site for transporting liquids by capillary forces [ 1 , 93 , 94 , 95 ].…”
Section: Different Materials and Preparation Methods For Microfluidic...mentioning
confidence: 99%
“…Paper has unique advantages over other materials in terms of low cost, flexibility and self-driven fluid pumping, thus making it widely used in various fields of wearable devices and human health monitoring [ 88 , 89 , 90 , 91 , 92 ]. Paper-based microfluidics is a fast-growing field because the inherently porous structure of paper provides a separate site for transporting liquids by capillary forces [ 1 , 93 , 94 , 95 ].…”
Section: Different Materials and Preparation Methods For Microfluidic...mentioning
confidence: 99%
“…In addition to the construction of paper based supercapacitor by spraying active ink on cellulose paper, the preparation of cellulose based conductive ink has also been studied in recent years. For example, Engquist et al [115,116] from Linköping University in Sweden reported two research efforts on inkjet printing of cellulosebased inks. As shown in Figure 12E, the team prepared a printable cellulose based ink by mixing CNF with conductive polymer PEDOT:PSS.…”
Section: Ink Jet Printingmentioning
confidence: 99%
“…(G)Based on the schematic diagram of solar self-charging equipment. (H)Electrochemical performance test of self-charging devices [116].…”
mentioning
confidence: 99%
“…Specifically, the conducting polymer poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), has been widely used in composites with cellulose [ 16 ] due to its high electronic and ionic conductivity, [ 24 ] high specific capacitance, and thermoelectric properties enabling the formation of active materials for supercapacitors, [ 25–30 ] thermoelectric generators, [ 31 ] sensors, [ 32 ] and actuators. [ 33 ] PEDOT:PSS is processed from an aqueous solution and therefore can be directly mixed with cellulose pulp or more refined forms of cellulose such as NFC to form functional composites with paper‐like structures or even 3D porous aerogels.…”
Section: Introductionmentioning
confidence: 99%
“…There are several examples in the literature where cellulose is combined with synthetic materials [11,12] such as inorganic nanoparticles, [13] ionic liquids, [14] carbon nanotubes, [15] and conducting polymers [16] for applications in non-traditional areas such as energy [17] and biomedical devices, [18] water treatment, [19] optical metamaterials, [20,21] and smart textiles. [22,23] Specifically, the conducting polymer poly(3,4ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), has been widely used in composites with cellulose [16] due to its high electronic and ionic conductivity, [24] high specific capacitance, and thermoelectric properties enabling the formation of active materials for supercapacitors, [25][26][27][28][29][30] thermoelectric generators, [31] sensors, [32] and actuators. [33] PEDOT:PSS is processed from an aqueous solution and therefore can be directly mixed with cellulose pulp or more refined forms of cellulose such as NFC to form functional composites with paper-like structures or even 3D porous aerogels.…”
Section: Introductionmentioning
confidence: 99%